Retrospective multicenter study of a clinicopathologic analysis of pseudomyxoma peritonei associated with ovarian tumors (KGOG 3005). Issue 5 (1st August 2008) - Lee, J. K.; Song, S. H.; Kim, I.; Lee, K. H.; Kim, B. G.; Kim, J. W.; Kim, Y. T.; Park, S. Y.; Cha, M. S.; Kang, S. B.
Abstract : The purpose of this study is to assess clinicopathologic features of pseudomyxoma peritonei (PMP) that has ovarian pathology and its relationship with the prognosis. From 1995 to 2004, the clinical records and follow-up data of 35 patients with PMP, which had primarily originated from the ovary, were collected from 11 institutes of gynecologic oncology in Korea and retrospectively analyzed. All patients had ovarian lesion histologically confirmed with PMP. The mean age at diagnosis was 53.7 years (range: 16–82 years). There were 25 (71.4%) patients with disseminated peritoneal adenomucinosis, 5 (14.3%) with peritoneal mucinous carcinomatosis with intermediate group, and 5 (14.3%) with peritoneal mucinous carcinomatosis. The clinical stages at diagnosis were IA in 2 patients, IIIB in 4, IIIC in 23, IV in 1, and unknown in 5. In preoperative tumor markers, the positive rates were 72% (CA125), 47.4% (CA19-9), and 84.6% (CEA). Thirty-four patients underwent surgical staging or cytoreduction, and then 27 patients (77%) received adjuvant chemotherapy that was given to patients in a nonuniform fashion. The 5-year survival for 35 patients was 87%. Survival rate was significantly lower in patients >50 years of age ( P = 0.002). Our data showed that age of the patient is the only significant prognostic factor in PMP that has ovarian lesion.